Additions to new species of foliicolous hyphomycetes from North-eastern U.P. - and D.K. AGARWAL, SHAMBHU KUMAR, RAGHVENDRA SINGH, VIVEK KUMAR PAL, P.P. UPADHYAYA (Indian Phytopathology, 2007)
This communication is devoted to the descriptions and illustrations of hitherto undescribed species of phytopathogenic hyphomycetes viz., Cereospora prosopidieola sp. novo (on Prosopis sp.: Mimosaceae), Cladosporium eyeadaeearum sp. novo (on Cyeas revoluta: Cycadaceae) and Taeniolella sapindii sp. novo (on Sapindus emarginatus: Sapindaceae) collected from North-eastern U.P. Morphotaxonomic determinations are based on comparison with allied taxa in question and current literature available.